Older people in a digitalized society : from marginality to agency - Rasi-Heikkinen, Päivi (Emerald Publishing Limited, 2022)
The digitalization of society is constructed as a necessary leap that governments and citizens need to take. However, with many older people lacking adequate digital competences to support their full participation in today's digitalized society, how is the marginalisation of older people in digital society socially constructed? How can we promote older people's digital inclusion and agency? Presenting case studies from Finland, one of the top performers in the supply and demand of digital public services, Older People in a Digitalized Society outlines internationally relevant implications for promoting the social construction of older people's agency. Delving into their digital competences, and use and non-use of Internet and eHealth technologies, Rasi-Heikkinen showcases the potential exclusionary effects of digitalization, and highlights the implications for digital inclusion practice and policy. Contesting the dominant discourses which suggest digital technologies and media play central roles in the learning, well-being, everyday life, and participation in society for individuals throughout their lifespan, Older People in a Digitalized Society addresses the digital gap faced by older generations that do not welcome digitalization, or even see it as a positive marginality: a choice that they have consciously made. Paying attention to how digitalization is a contested issue constructed with various, ambivalent, and paradoxical representations, Rasi-Heikkinen shines an important light on how older people are constructed as being on the margins of digitalization by researchers and the media.
Keywords: Computers and older people.; Computer literacy.; Marginality, Social.; Older people -- Social conditions -- 21st century.; Social Science -- Sociology -- General.; Sociology.; elektronické knihy; electronic books